2023
DOI: 10.1038/s41598-023-41224-z
|View full text |Cite
|
Sign up to set email alerts
|

An enzyme-based system for extraction of small extracellular vesicles from plants

Qing Zhao,
Guilong Liu,
Fubin Liu
et al.

Abstract: Plant-derived nanovesicles (NVs) and extracellular vesicles (EVs) are the next generation of nanocarrier platforms for biotherapeutics and drug delivery. EVs exist not only in the extracellular space, but also within the cell wall. Due to the limitations of existing isolation methods, the EVs extraction efficiency is low, and a large amount of plant material is wasted, which is of concern for rare and expensive medicinal plants. We proposed and validated a novel method for isolation of plant EVs by enzyme degr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Some researchers have compared the wall-breaking and osmotic centrifugation methods, and found that Arabidopsis EVs obtained by vacuum osmosis method had smaller particle size, lower potential, smaller density and higher lipid film thickness ( Liu et al, 2020 ). Zhao et al suggested employing cellulase and pectinase enzymes to facilitate the digestion and disruption of cell walls to obtain the EVs derived from Morindae Officinalis Radix (Bajitian in Chinese) ( Zhao et al, 2023 ).…”
Section: Separation Methods For Chm Vesiclesmentioning
confidence: 99%
See 2 more Smart Citations
“…Some researchers have compared the wall-breaking and osmotic centrifugation methods, and found that Arabidopsis EVs obtained by vacuum osmosis method had smaller particle size, lower potential, smaller density and higher lipid film thickness ( Liu et al, 2020 ). Zhao et al suggested employing cellulase and pectinase enzymes to facilitate the digestion and disruption of cell walls to obtain the EVs derived from Morindae Officinalis Radix (Bajitian in Chinese) ( Zhao et al, 2023 ).…”
Section: Separation Methods For Chm Vesiclesmentioning
confidence: 99%
“…The Bicinchoninic Acid Assay (BCA) is utilized to determine the concentration of protein in CHM-EVLP, while NTA or nFCM techniques are employed to measure particles concentration, which is subsequently converted into the number of particles per milligram of vesicles protein (particles/mg) ( Zhao et al, 2023 ).…”
Section: Quality Control Of Chm-evlpmentioning
confidence: 99%
See 1 more Smart Citation
“…Simultaneously, this combination approach is applicable for isolating PDNVs with high purity and stability from the model plant Arabidopsis . Additionally, several experts have suggested a novel pretreatment technique for isolating NVs from plants (Zhao et al 2023b). The plant cell walls were broken down using specific digestive enzymes that targeted the primary components of the wall.…”
Section: Extraction and Identificationmentioning
confidence: 99%